Improving Area Coverage of Wireless Sensor Networks Via Controllable Mobile Nodes: a Greedy Approach - Massimo Vecchio; R. López-Valcarce (Journal of Network and Computer Applications, 2015)
Reliable wide-area monitoring with Wireless Sensor Networks (WSNs) remains a problem of interest: simply deploying more nodes to cover wider areas is generally not a viable solution, due to deployment and maintenance costs and the increase in radio interference. One possible solution gaining popularity is based on the use of a reduced number of mobile nodes with controllable trajectories in the monitored field. In this framework, we present a distributed technique for iteratively computing the trajectories of the mobile nodes in a greedy fashion. The static sensor nodes actively assist the mobile nodes in this task by means of a bidding protocol, thus participating towards the goal of maximizing the area coverage of the monitored field. The performance of the proposed technique is evaluated on various simulation scenarios with different number of mobile and static nodes in terms of achieved coverage and mean time to achieve X% coverage. Comparison with previous state-of-the-art techniques reveals the effectiveness and stability of the proposed method.
Keywords: compass; wsn